Aryl hydrocarbon receptor negatively regulates expression of the plakoglobin gene (jup) - Procházková, Jiřina; Kabátková, Markéta; Šmerdová, Lenka; Pacherník, Jiří; Sykorová, Dominika; Kohoutek, Jiří; Šimečková, Pavlína; Hrubá, Eva; Kozubík, Alois; Machala, Miroslav; Vondráček, Jan (Toxicological sciences, 2013)
Plakoglobin is an important component of intercellular junctions, including both desmosomes and adherens junctions, which is known as a tumor suppressor. Although mutations in the plakoglobin gene (Jup) and/or changes in its protein levels have been observed in various disease states, including cancer progression or cardiovascular defects, the information about endogenous or exogenous stimuli orchestrating Jup expression is limited. Here we show that the aryl hydrocarbon receptor (AhR) may regulate Jup expression in a cell-specific manner. We observed a significant suppressive effect of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a model toxic exogenous activator of the AhR signaling, on Jup expression in a variety of experimental models derived from rodent tissues, including contact-inhibited rat liver progenitor cells (where TCDD induces cell proliferation), rat and mouse hepatoma cell models (where TCDD inhibits cell cycle progression), cardiac cells derived from the mouse embryonic stem cells, or cardiomyocytes isolated from neonatal rat hearts. The small interfering RNA (siRNA)-mediated knockdown of AhR confirmed its role in both basal and TCDD-deregulated Jup expression. The analysis of genomic DNA located ~2.5kb upstream of rat Jup gene revealed a presence of evolutionarily conserved AhR binding motifs, which were confirmed upon their cloning into luciferase reporter construct. The siRNA-mediated knockdown of Jup expression affected both proliferation and attachment of liver progenitor cells. The present data indicate that the AhR may contribute to negative regulation of Jup gene expression in rodent cellular models, which may affect cell adherence and proliferation.
Keywords: Gene Expression Regulation; potkani inbrední F344; down regulace; sekvence nukleotidů; receptory aromatických uhlovodíků; Cell Line; liver progenitor cells; plakoglobin; kvantitativní polymerázová řetězová reakce; Cell Proliferation; Cloning, Molecular; cardiomyocytes.; klonování DNA; promotorové oblasti (genetika); DNA Primers; gama-katenin; dioxin; Polychlorinated Dibenzodioxins; Real-Time Polymerase Chain Reaction; buněčná adheze; krysa rodu Rattus; aryl hydrocarbon receptor; Animals; Down-Regulation; gamma Catenin; desmosomes; zvířata; regulace genové exprese; Promoter Regions, Genetic; Rats; DNA primery; buněčné linie; proliferace buněk; polychlorované dibenzodioxiny; Rats, Inbred F344; Base Sequence; cell proliferation; Receptors, Aryl Hydrocarbon; Cell Adhesion